Determination of double-K fracture toughness parameters of thermally treated granite using notched semi-circular bending specimen. (1st March 2020) - Yin, Tubing; Wu, You; Li, Qiang; Wang, Chao; Wu, Bingqiang
Highlights: The double-K fracture parameters of heated granite specimens were measured using notch semi-circular specimens. The acoustic emission behaviours of heated granite specimens under the whole loading processes were recorded and discussed. The double-K fracture parameters fit with the acoustic emission characterises. The double-K fracture parameters can be well used to explain the fracture processes of heated granite. The temperature dependence of double-K fracture parameters are discussed. Abstract: The safety of cracked rock structures after thermal treatment is the concern of many existing engineering programs. To obtain a deep understanding of rock fracture process, mode I fracture tests are carried out on thermally treated granite (from 25 °C to 800 °C) using notched semi-circular bending (NSCB) specimens in this paper. An acoustic emission (AE) technique is employed to monitor the real-time AE activities during the whole deformation process. The double-K parameters extracted from the double-K fracture model are applied to depict the fracture process of the heat-treated granite NSCB specimens. When the temperature rises from 25 °C to 800 °C, rock density, porosity, elastic modulus, and Poisson's ratio all show variations to some extent. The heat treatment decreases the rock density, elastic modulus, and Poisson's ratio, while it increases the rock porosity. Fracture tests show that the rock fracture behaviours gradually change from brittle fracture to ductile fracture when the thermal treatment temperature exceeds 300 °C: i.e., the start temperature of brittle–ductile transition. AE results show that the crack initiation load and peak load agree well with the AE activity characteristics during the entire loading process. It is observed that the crack initiation fracture toughness K IC ini and the unstable fracture toughness K IC un from double-K fracture model can be successfully applied to describe the rock fracture. When the temperature ranges from 25 °C to 300 °C, K IC ini and K IC un are not sensitive to temperature. However, as temperature ascends over 300 °C, K IC ini and K IC un almost linearly decrease with temperature. The decline in K IC ini and K IC un demonstrates that the rock has gradually lost its ability to withstand cracking from initiation and propagation. This paper aims to better understand the mode I fracture of thermally treated rocks and initially explore and determine the double-K fracture toughness parameters of thermally treated rocks with NSCB specimens.